2021
DOI: 10.1186/s12955-021-01726-8
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of social support on the relationship between perceived stress and quality of life among shidu parents in China

Abstract: Background “Loss-of-only-child family” refers to the family in which the only child died and the mother has passed her child-bearing age. The parents who are unable to reproduce or do not foster other children are known as “shidu parents” in China. This study aimed to estimate the quality of life (QOL) and the mediating role of social support between perceived stress and QOL in Chinese shidu parents. Methods 502 shidu parents were recruited in Shen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This result is insightful given that studies (Jenaro et al, 2020;Obuna et al, 2019;Wang et al, 2021) had shown that when families perceive the caring for their member with IDD as stressful, it might precipitate psychological, social, and economic pressures on such families. Interestingly, for the participants in the study, when the perceived stress was high or average, a unit increase in family support was enough to stabilize their FQOL.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This result is insightful given that studies (Jenaro et al, 2020;Obuna et al, 2019;Wang et al, 2021) had shown that when families perceive the caring for their member with IDD as stressful, it might precipitate psychological, social, and economic pressures on such families. Interestingly, for the participants in the study, when the perceived stress was high or average, a unit increase in family support was enough to stabilize their FQOL.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, lack of essential support from family could affect their quality of life (Alsubaie et al, 2019;Brown et al, 2006;Dey & Amponsah, 2020). More importantly, their perceived stress from their daily hassles may mediate the relation between how their family support influences their quality of life (Wang et al, 2021). However, what is unclear is to what extent will perceived stress moderate this relation.…”
Section: Perceived Stress As a Moderatormentioning
confidence: 99%
“…Affected by the one-child policy, there are a large number of Shidu parents in rural China and they are generally suffering from mental health problems (Wang, Lin, et al, 2021;Zhang et al, 2020;). After losing a child, they may develop suicidal ideation or even suicidal behaviour .…”
Section: Public Health and Clinical Implications Of Current Researchmentioning
confidence: 99%
“…These only-child families are at the risk of being Shidu families (Wang, Zhang, et al, 2021). Meanwhile, according to previous studies, the mean age of these Shidu parents are above 60 years old (Eli et al, 2020;Shi et al, 2019;Wang, Lin, et al, 2021;Zhang et al, 2020). The rapid aging population will undoubtedly affect these elderly Shidu parents (Wang, Zhang, et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation